2008
DOI: 10.1080/15332980802072546
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the Individual Trauma of Domestic Violence: Challenges for Mental Health Professionals

Abstract: A clear link exists between domestic violence and mental health problems for women. Depression, trauma symptoms, and suicide attempts are issues that seriously undermine the emotional well-being of women who have been subjected to violence and abuse from their partner or ex-partner. This paper draws on a research project that highlighted the mental health issues for women using domestic violence services and raised a number of pertinent problems for policy and practice in this area. Bringing services for survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A study by Humphreys [ 11 ] to assess psychiatrists’ knowledge of mental health legislation indicated inadequate knowledge on the foundational and essential areas within the mental health legislation. A similar finding was evidenced in this study as health workers were not adequately aware of certain aspects of the Mental Health Act and specific regulations guiding the issuance and usage of Certificate of Urgency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Humphreys [ 11 ] to assess psychiatrists’ knowledge of mental health legislation indicated inadequate knowledge on the foundational and essential areas within the mental health legislation. A similar finding was evidenced in this study as health workers were not adequately aware of certain aspects of the Mental Health Act and specific regulations guiding the issuance and usage of Certificate of Urgency.…”
Section: Discussionmentioning
confidence: 99%
“…In a study undertaken in Scotland which examined psychiatrists’ knowledge of mental health legislation. The study findings revealed that knowledge of most basic definitions and fundamental areas was limited [ 11 ]. A study that was carried out to determine the levels of knowledge of Section 136, The Mental Health Act 1983 in the UK by Lynch et al [ 12 ] also found a majority of respondents having low knowledge of the Act 1983.…”
Section: Introductionmentioning
confidence: 99%
“…Current commentators also point to the orientation of health services towards acute care services (Hague & Mullender, 2006;Humphreys, 2008;Wilson, Silberberg, Brown, & Yaggy, 2007) and the structural constraints on health service providers, which serve to meet the interests of the dominant professional groups (Davis & Harsh, 2001;Plichta, 2007), and suggest that this has led to women being further abused within the health care system, by health care providers and bureaucrats who have competing interests related to health care resource usage (Kim & Motsei, 2002;Plichta, 2007). To unravel these factors is complex and requires deconstructing the lens that currently informs knowledge and which orients and provides structure to health service provision.…”
mentioning
confidence: 98%